2010
DOI: 10.1037/a0019500
|View full text |Cite
|
Sign up to set email alerts
|

Together in pain: Attachment-related dyadic processes and posttraumatic stress disorder.

Abstract: We used actor-partner interdependence modeling to explore associations among attachment-related dyadic processes, posttraumatic stress disorder (PTSD) in war veterans, and secondary traumatic stress (STS) in their wives. A sample of 157 Israeli couples (85 former prisoners of war and their wives and a comparison group of 72 veterans not held captive and their wives) completed self-report scales assessing attachment insecurities (anxiety, avoidance) and PTSD symptoms. For both groups of veterans and their wives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 82 publications
7
72
1
1
Order By: Relevance
“…The wives describe in detail the tremendous negative effects on the following aspects of their lives: daily functioning, economic difficulties, lack of couple intimacy, poor parenthood and very little social life and leisure time. These results corroborate other studies, indicating the negative effects of the husbands' traumaon the entire family (Ben Arzi, Solomon, & Dekel, 2000;Bramsen, Van der Ploeg, & Twisk, 2002;Galovski & Lyons, 2004;Ein-Dor, Doron, Mikulincer, Solomon, & Shaver, 2010;Ray & Nanstone, 2009;Solomon et al, 2011). However, these studies mainly focused on levels of various symptoms compared to control groups.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The wives describe in detail the tremendous negative effects on the following aspects of their lives: daily functioning, economic difficulties, lack of couple intimacy, poor parenthood and very little social life and leisure time. These results corroborate other studies, indicating the negative effects of the husbands' traumaon the entire family (Ben Arzi, Solomon, & Dekel, 2000;Bramsen, Van der Ploeg, & Twisk, 2002;Galovski & Lyons, 2004;Ein-Dor, Doron, Mikulincer, Solomon, & Shaver, 2010;Ray & Nanstone, 2009;Solomon et al, 2011). However, these studies mainly focused on levels of various symptoms compared to control groups.…”
Section: Discussionsupporting
confidence: 81%
“…Most studies that examine veterans with PTSD and the effects on the family (e.g., Ein-Dor et al, 2010;Gold et al, 2007) have not examined this period of disillusionment, or recognition. Our study suggest that this stage, which might take many months (sometime even years) is characterized by lack of understanding and information, confusions, shame and efforts to hide the husband's situation from close family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although talking is often the first step toward integration and healing, "mistrust" of those who have not served in the military (Danish & Antonides, 2009) makes it less likely that combat veterans will be willing to talk about their most difficult war experiences with a therapist who is not a veteran. The forces of stigma and isolation thus combine to trap veterans in the avoidant coping practices that so many of them rely onpractices that can augment and sustain the feelings of distress and sorrow that they are meant to suppress (Ein-Dor, Doron, Solomon, Mikulincer, & Shaver, 2010;Romero et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Family systems and attachment-informed research is available on military families, especially American veterans of the Iraq and Afghanistan wars (Pemberton, Kramer, Borrego, & Owen, 2013; Riggs & Riggs, 2011) and Israeli soldiers, veterans, and prisoners of war (Cohen, Zerach, & Solomon, 2011; Ein-Dor, Doron, Solomon, Mikulincer, & Shaver, 2010; Zerach, Greene, Ein-Dor, & Solomon, 2012). These studies found negative family dynamics, especially when the veteran parents had PTSD.…”
Section: Introductionmentioning
confidence: 99%